2015
DOI: 10.1002/gcc.22255
|View full text |Cite
|
Sign up to set email alerts
|

Systematic investigation of CMTM family genes suggests relevance to glioblastoma pathogenesis and CMTM1 and CMTM3 as priority targets

Abstract: The novel CKLF-like Marvel Transmembrane Domain-containing gene family (CMTM) consists of 8 members (CMTM1-8). As little is known about the oncogenic impact of these genes, we aimed to systematically investigate the relevance of CMTMs to glioblastoma pathogenesis. We performed mRNA expression analyses and survival correlations in glioblastoma patients. Moreover, we analyzed the impact of RNAi-based silencing and overexpression of CMTM family genes on tumor cell proliferation and invasion in vitro. CMTMs appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 25 publications
2
34
0
Order By: Relevance
“…This family serves major roles in the immune system, male reproductive system and hematopoiesis systems. On the basis of the in‐depth studies in recent years performed by various research groups, a close association between CMTMs and the initiation, development and metastasis of tumors has been demonstrated . A number of studies have shown that CMTM 3, 4, 5, and 8 have been extensively studied as tumor suppressors in multiple types of tumor .…”
Section: Discussionmentioning
confidence: 99%
“…This family serves major roles in the immune system, male reproductive system and hematopoiesis systems. On the basis of the in‐depth studies in recent years performed by various research groups, a close association between CMTMs and the initiation, development and metastasis of tumors has been demonstrated . A number of studies have shown that CMTM 3, 4, 5, and 8 have been extensively studied as tumor suppressors in multiple types of tumor .…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, CMTM3 regulated the STAT3/Twist1/EMT signaling pathway (13). Although the positive role of CMTM3 in cancer progression has been demonstrated (25), it is well accepted to be a tumor suppressor. Previous studies have suggested that promoter hypermethylation is involved in the decreased expression of CMTM3 in various types of cancer, including gastric, colorectal and breast cancer (11,12,26).…”
Section: Discussionmentioning
confidence: 99%
“…These findings all proved that CMTM3 had a suppressive function in tumor progression. Only one study presented the oncogenic effects of CMTM3 in glioblastoma by Delic, in which CMTM1, 3, and 7 were proved to promote the abilities of tumor cell invasion, and higher CMTM1 and 3 expressions significantly correlated with shorter overall survivals [26]. To further explore the potential tumor-suppressive mechanisms of CMTM3 in cancers, several studies were performed and concluded as follows: (i) the silence of CMTM3 was due to aberrant promoter CpG methylation that could be reversed by pharmacologic demethylation [16,[27][28][29]; (ii) the expression of MMP2 and the phosphorylation of Erk1/2 were decreased when CMTM3 was restored [13,15]; (iii) CMTM3 induced a cell cycle arrest of G2 phase and apoptosis by upregulating the expression of p21 and increasing the cleavage of caspase 9, 8, 3 and PARP [16]; (iv) CMTM3 inhibited EMT through the STAT3/Twist1/EMT or JAK2/ STAT3 signaling pathway [14,17].…”
Section: Discussionmentioning
confidence: 99%